Agronomic and technological evaluation of sugar cane varieties in the Cariri region of Ceará state, Brazil - Filho, Francisco Carlos; Távora, Francisco José Alves Fernandes; Cruz, Hilton Luis Leite (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted on a clay alluvial eutrofic soil, in the Cariri area of the Southern Region of the State of Ceará, Brazil, with the purpose of studying the behavior of the following sugar cane varieties: Co 419, IANE 55-17, CB 45-3, CP 51-22, 8 4362, CP 60-1, Co 1007, Co 997, CP 53-76 and NA 56-79. A randomized complete block design with split plots was used with varieties as the whole plot, and harvests as the sub-plot, with four replications. The experiment was planted in August 1978, and four harvests were performed at 12 months interval. The varieties NA 56-79, CP 60-1 and CB 45-3 showed the highest cane and sugar production per hectare. In industrial yield (kg of recovered sugar per tone), in the harvest average, all of the varieties behaved satisfatorily, being NA 56-79, CP 53-76, C8 45-3 and Co 997 the best ones. The ratoon crop 2nd to 4td harvests-showed an increase in the number of tillers, and better industrial characteristics than those plants harvested in the first year after planting. On the other hand, the first harvest showed higher production of recovered sugar per hectare than the ratoon crops.